Comparison of the Pathway to the Inner Ear Between Postauricular and Intramuscular Injection of Dexamethasone in Guinea Pigs - Chen, Aiping; Liu, Wenwen; Xu, Lei; Hou, Zhiqiang; Fan, Zhaomin; Wang, Haibo; Wang, Mingming (Frontiers in Neurology, 2022)
Background: Postauricular injection as a local therapy has been confirmed to be effective for inner ear diseases. However, the mechanism for the drugs entering the inner ears remains unknown. This study aims to compare the distribution of dexamethasone by intramuscular injection with that by postauricular injection, and explore the pathway of the drugs entering the inner ears. Methods: An in vivo optical imaging system was used to conduct a time course observation to compare the distribution of dexamethasone by intramuscular injection with that by postauricular injection in male guinea pigs. The drug availability in the tympanic mucosa, tympanum, endolymphatic sac and cochlea was observed by a confocal laser scanning microscope. Results: The local fluorescent intensity by postauricular injection was significantly higher in the inner ears, and lower in partial peripheral organs, than that by the intramuscular injection. The drug metabolism by postauricular injection exhibited an obviously sustained release effect in the inner ears. Drugs by postauricular injection might enter the endolymphatic sac through the posterior auricular artery and occipital artery, as well as the connections of the mastoid emissary vein, sigmoid sinus and endolymphatic sac. Conclusion: More drugs concentrated in the inner ear for longer therapeutic time and less systemic delivery implied more effective and less risk of side effects through postauricular injection than intramuscular injectionsafer for the treatment of inner ear diseases.